2012
DOI: 10.1111/j.1464-410x.2012.11346.x
|View full text |Cite
|
Sign up to set email alerts
|

Does radical nephrectomy increase the risk of erectile dysfunction compared with partial nephrectomy? A cohort analysis

Abstract: What ' s known on the subject? and What does the study add? Erectile dysfunction (ED) is a form of endothelial dysfunction that is prevalent in patients with chronic kidney disease (CKD). We hypothesized that partial nephrectomy (PN) would limit development of ED compared with radical nephrectomy (RN), primarily due to renal function preservation, and found that patients undergoing RN had signifi cantly higher de novo ED compared with a contemporary, well-matched cohort undergoing PN; in addition to RN, hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…A study examining the risk of ED following radical versus partial nephrectomy found a significantly higher rate of de novo ED in those subjected to radical surgery (51). This suggests that a greater reduction in nephron mass resulted in a greater risk of ED development.…”
Section: Ed In Ckdmentioning
confidence: 99%
“…A study examining the risk of ED following radical versus partial nephrectomy found a significantly higher rate of de novo ED in those subjected to radical surgery (51). This suggests that a greater reduction in nephron mass resulted in a greater risk of ED development.…”
Section: Ed In Ckdmentioning
confidence: 99%
“…To focus on the evaluation of erectile function, the severity of ED was graded as no (26-30), mild (22)(23)(24)(25), mild to moderate (17)(18)(19)(20)(21), moderate (11)(12)(13)(14)(15)(16) or severe (6-10) using the IIEF-erectile function domain data according to a previous study. 11 Five (7.7%), ten (15.4%), eleven (16.9%), nine (13.8%) and thirty (46.2%) patients were categorized as no, mild, mild to moderate, moderate and severe ED, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the significant increase in CKD mortality due to medical causes, 6 surgically induced CKD did not necessarily correlate with increased mortality in a recent large study. 16 If the issue is limited to the relationship between surgical CKD and ED, then there are few studies available in which a comparative evaluation between RN and partial nephrectomy, 17 and ED prevalence in a donor nephrectomy cohort 18 are discussed. Because surgical CKD is a recent unique entity, its clinical manifestations are not entirely known.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies with NSS in adults have suggested improved long-term renal function, cardiovascular health, decreased osteoporosis, and increased overall survival while maintaining equivalent oncological outcomes. [1617] More data in the pediatric population are needed to see if the results in adults can be replicated in this group as well. Vanden Berg et al .…”
Section: Discussionmentioning
confidence: 99%